KEBIJAKAN PENGEMBANGAN PERPUSTAKAAN UMUM DI KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU TAHUN 2011-2013 - Sari, Dwi Puspita; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study is intended to determine the role of the Government in implementing the policy, and to know the role of the Office of Library and Regional Archives in implementing the policy. This study focused on Libraries and Library and Archive Office of Karimun regency, whose scope lies in Karimun Riau Islands province, because given the most complex issues contained in the library. These problems include lack of public interest, infrastructure, and human resources. With the formulation of research problems that How public library policy development in Karimun and the factors that affect the implementation of the policy of public library development in Karimun. In the development of the library, the library has been no policy for the region applicable regulations especially those concerning libraries in Karimun, the study aims to identify and analyze policy public library development in Karimun.The research method is qualitative descriptive research data collection is done by observation, interviews and documentation.From the results of research in the field indicates that the Office of Library and Regional Archives Karimun not have a policy of development of a library of standard, so that the public library is in Karimun still referring to existing policies at central and regional administration Riau, a policy that is in Karimun only Local Rules and Regulations in the form of Regents that a technical course. The factors that affect the implementation of the policy of development of public libraries in Karimun, through the theory of former Van Meter and Van Horn, namely: Target and policy standards, performance policies, resources, communication between implementing agencies, Characteristics implementing agencies, economic environment, social and politics and the attitude of the implementers. In this study, the authors conclude that the Local Government does not currently have a policy regarding the library so that local governments do not yet have its own guidelines in terms of policy particularly in view of the public library in Karimun. However, should the regional government should implement a specific policy of the library.Keywords: Policy, Development, Public Library and Government Authority.